Enhanced Cas12a editing in mammalian cells and zebrafish. Issue 8 (20th March 2019) - Liu, Pengpeng; Luk, Kevin; Shin, Masahiro; Idrizi, Feston; Kwok, Samantha; Roscoe, Benjamin; Mintzer, Esther; Suresh, Sneha; Morrison, Kyle; Frazão, Josias B; Bolukbasi, Mehmet Fatih; Ponnienselvan, Karthikeyan; et al.
Abstract: Type V CRISPR–Cas12a systems provide an alternate nuclease platform to Cas9, with potential advantages for specific genome editing applications. Here we describe improvements to the Cas12a system that facilitate efficient targeted mutagenesis in mammalian cells and zebrafish embryos. We show that engineered variants of Cas12a with two different nuclear localization sequences (NLS) on the C terminus provide increased editing efficiency in mammalian cells. Additionally, we find that pre-crRNAs comprising a full-length direct repeat (full-DR-crRNA) sequence with specific stem-loop G-C base substitutions exhibit increased editing efficiencies compared with the standard mature crRNA framework. Finally, we demonstrate in zebrafish embryos that the improved LbCas12a and FnoCas12a nucleases in combination with these modified crRNAs display high mutagenesis efficiencies and low toxicity when delivered as ribonucleoprotein complexes at high concentration. Together, these results define a set of enhanced Cas12a components with broad utility in vertebrate systems.